2017
DOI: 10.1111/ele.12819
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled responses of soil bacteria and their invertebrate consumer to warming, but not freeze–thaw cycles, in the Antarctic Dry Valleys

Abstract: Altered temperature profiles resulting in increased warming and freeze-thaw cycle (FTC) frequency pose great ecological challenges to organisms in alpine and polar ecosystems. We performed a laboratory microcosm experiment to investigate how temperature variability affects soil bacterial cell numbers, and abundance and traits of soil microfauna (the microbivorous nematode Scottnema lindsayae) from McMurdo Dry Valleys, Antarctica. FTCs and constant freezing shifted nematode body size distribution towards large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
(150 reference statements)
1
19
1
1
Order By: Relevance
“…Body size distributions may reveal ecological patterns undetected by other analyses (Andriuzzi, Pulleman, Cluzeau, & Pérès, ; Knox et al., ; Lindo, ; Zhao et al., ), but our results show that simpler metrics of abundance and community structure are essential to interpret them correctly. In the high‐OM site, the intercept of the abundance–mass relationship was higher in grazed than ungrazed soil, but rather than a sign of community downsizing (e.g., as in Lindo, ) in this case, it was an artefact of the much lower abundance in grazed than ungrazed Site 3 (i.e., nematodes across the entire size spectrum were less numerous); therefore, we focused on the slopes.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Body size distributions may reveal ecological patterns undetected by other analyses (Andriuzzi, Pulleman, Cluzeau, & Pérès, ; Knox et al., ; Lindo, ; Zhao et al., ), but our results show that simpler metrics of abundance and community structure are essential to interpret them correctly. In the high‐OM site, the intercept of the abundance–mass relationship was higher in grazed than ungrazed soil, but rather than a sign of community downsizing (e.g., as in Lindo, ) in this case, it was an artefact of the much lower abundance in grazed than ungrazed Site 3 (i.e., nematodes across the entire size spectrum were less numerous); therefore, we focused on the slopes.…”
Section: Discussioncontrasting
confidence: 62%
“…Such research gaps are particularly wide for soil animals, which is at odds with a growing number of studies on how their body size determines ecosystem processes or responses to global change (de Graaff, Adkins, Kardol, & Throop, 2015;Knox et al, 2017;Lindo, 2015;Moretti et al, 2016). Body size varies enormously in soil fauna, as reflected by the conventional sorting of soil invertebrates in microfauna, mesofauna and macrofauna, of demonstrated functional importance (Cole, Bradford, Shaw, & Bardgett, 2006;de Graaff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Field observations and a numerical active layer thermal model are used to elucidate physical controls on the active layer thermodynamic regime. Results of this research refine the Knox et al () hypothesis by clarifying expectations of how regional climate change may alter the frequency, rate, and spatial patterning of active layer freeze‐thaw events. Additionally, field‐observed freezing rates provide a quantitative benchmark for planning future laboratory studies employing cultured nematodes.…”
Section: Introductionsupporting
confidence: 77%
“…Ten‐centimeter freezing rate plotted as a function of 15 day mean antecedent freezable soil moisture at 15 cm. For reference, the freezing rate applied to laboratory cultured S. lindsayae in the Knox et al () study is shown by a black dashed line.…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased summer temperatures in the region will initiate more frequent freeze‐thaw cycles in dry soils, increasing mortality of the dominant invertebrate (Knox et al. , ). Snow cover in the McMurdo Dry Valleys is patchy and ephemeral, and soils completely lack plant cover and ecosystem engineering macrofauna, thereby they are devoid of abiotic and biotic buffers that, in other ecosystems, can mitigate the impact of harsh atmospheric conditions (Pauli et al.…”
Section: Discussionmentioning
confidence: 99%